Multi-Parameter Analysis of Biobanked Human Bone Marrow Stromal Cells Shows Little Influence for Donor Age and Mild Comorbidities on Phenotypic and Functional Properties - Andrzejewska, Anastazja; Catar, Rusan; Schoon, Janosch; Qazi, Taimoor Hasan; Sass, Frauke Andrea; Jacobi, Dorit; Blankenstein, Antje; Reinke, Simon; Krüger, David; Streitz, Mathias; Schlickeiser, Stephan; Richter, Sarina; et al. (Frontiers in Immunology, 2019)
Heterogeneous populations of human bone marrow-derived stromal cells (BMSC) are among the most frequently tested cellular therapeutics to treat degenerative and immune disorders, which occur predominantly in the aging population. Currently, it is unclear, if advanced donor age and commonly associated comorbidities affect the properties of ex vivo-expanded BMSCs. Thus, we stratified cells from adult and elderly donors from our biobank (n=10 and n=13, mean age 38 and 72 years) and compared their phenotypic and functional performance, using multiple assays typically employed as minimal criteria for defining multipotent mesenchymal stromal cells (MSCs). We found that BMSCs from both cohorts meet the MSC standard criteria, exhibiting similar morphology, growth kinetics, gene expression profiles, pro-angiogenic and immunosuppressive potential, and the capacity to differentiate toward adipogenic, chondrogenic and osteogenic lineage. We found no substantial differences between cells from adult and elderly cohorts. As positive controls, we studied the impact of in vitro aging and inflammatory cytokine stimulation. Both conditions clearly affected the cellular properties independent of donor age. We conclude that in vitro aging rather than in vivo donor aging influences BMSC characteristics.